THE EXPRESSIONS OF CORRECTIVE FEEDBACK IN SECOND LANGUAGE CLASSROOM - Sulistyani Sulistyani (English Teaching Journal : A Journal of English Literature, Language and Education, 2014)
This study aims to review the teacher’s expressions which constitute teacher’s corrective feedbacks (CFs) in oral production and examine the ways the teachers' expression revealing teacher’s CFs. The data are in the forms of teachers' utterances obtained from four research articles. The result shows that teacher' expressions which  constitute CFs cover explicit correction, recast, clarification request, metalinguistic, elicitation, and repetition. While the ways which reveal teacher’s CFs are found to be reduction, negation, and  expansion. The area to be corrected commonly involves phonological, grammatical, and lexical errors. So, it can be concluded that in a second language classroom instruction, teacher’s CFs expressions lead learners' erroneous utterances to be resolved because by saying "Sorry?" (clarification request), a teacher implicitly asks a language learner to reformulate what he has just been said which is usually called repair. Thus, it implies that the teacher’s CFs expressions in a second language classroom instruction are facilitative to resolve learners' problematic linguistic accuracy. In Indonesia, where English is used as foreign language, CFs are important to be practiced. Therefore, CF’s expressions are necessary to be introduced as a model to practice for the improvement of the linguistic competence especially in English speaking as it is assumed that excellence in speaking is expected to increase Indonesian human capital particularly in global competition and international communication.